1980
DOI: 10.2307/1936755
|View full text |Cite
|
Sign up to set email alerts
|

A Physiological Basis for Niche Separation Between Agropyron Smithii (C3) and Bouteloua Gracilis (C4)

Abstract: Agropyron smithii (a C3 species) and Bouteloua gracilis (a C4 species) occur in the same habitat of the shortgrass prairie ecosystem in northeastern Colorado. The hypothesis tested in this study was that the two species differ in their fundamental niches partly as a function of their different physiological responses to temperature and moisture gradients. Growth and gas exchange patterns were measured on plants grown in controlled—environment chambers at cool (20°/15°C) and warm (35°/15°C) temperatures. Total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
91
1

Year Published

1981
1981
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(97 citation statements)
references
References 48 publications
(54 reference statements)
5
91
1
Order By: Relevance
“…Second, C4 grasses are strong nitrogen competitors in our system (25) and have many traits that make them dominant competitors for nitrogen. C4 grasses have higher nutrient-use efficiencies, greater water-use efficiencies (31,32), and lower tissue nitrogen concentrations (32) than C3 grasses. At Cedar Creek Natural History Area, a comparison of two C4 and three C3 grass species showed that C4 grasses more strongly reduced midsummer soil nitrate (27), had lower tissue nitrogen concentration, greater nitrogen-use efficiency, greater net productivity, and greater proportion of biomass below ground (33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, C4 grasses are strong nitrogen competitors in our system (25) and have many traits that make them dominant competitors for nitrogen. C4 grasses have higher nutrient-use efficiencies, greater water-use efficiencies (31,32), and lower tissue nitrogen concentrations (32) than C3 grasses. At Cedar Creek Natural History Area, a comparison of two C4 and three C3 grass species showed that C4 grasses more strongly reduced midsummer soil nitrate (27), had lower tissue nitrogen concentration, greater nitrogen-use efficiency, greater net productivity, and greater proportion of biomass below ground (33).…”
Section: Discussionmentioning
confidence: 99%
“…Third, C3 grasses attain peak biomass in the cool times of year, i.e., spring and fall (32,36), whereas C4 grasses grow most actively in the hot summer months (31). These differences are attributable to their different photosynthetic pathways (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…As long as there is sufficient diversity of microsites at a given locale, both C 3 and C 4 species could coexist. Temporal separations of C 3 and C 4 plants in communities have been measured and found to be significant in Wyoming (Boutton et al 1980), Colorado (Kemp and Williams 1980), and South Dakota (Ode et al 1980). These studies found C 3 species to be dominant, in either biomass or frequency, in the spring.…”
Section: Introductionmentioning
confidence: 95%
“…I produced about 400 kg ha-r more biomass above-ground than short-grass native range but about 100 kg ha-l less of total plant yield (Redente et al 1989). Net primary production on ungrazed Agropyron-Koeleria, Agropyron (smithii)-Stipa (viridula), and Stipa-BoutelouaAgropyron sites was about 7,000, 7 ,820, and 12,600 kg ha-r, respectively, with about 80% below ground (Sims and Coupland 1979 (Smoliak 1986 more readily and produced almost 3 times more biomass in a warm environment (Kemp and Williams 1980). The offsetting growth between the species may be a strategy for reducing interspecifi c competition (Williams 1974) and increasing community production (Lorenz and Rogler 1972)butthe most visible effect is on the community structure.…”
mentioning
confidence: 99%